Design of Students Sports Club in Bali Province (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2019)
The specific objectives of this development research were (1) designing the concept of a student sports club in Bali, (2) developing the design of the student sports club model in Bali, and the guidelines for the establishment of a student sports club in Bali. This research used R&D design with procedure and product trial. The applied product of the research were 1) recommendation of analysis of the needs of the education, sports, and youth offices on the concept of a student sports club, (2) the design of the student sports club model in Bali, and (3) guidance on the formation of a student sports club in Bali. Applied products produced are expected to overcome the obstacles and difficulties experienced by education, sports, and youth offices to handle student sports clubs in Bali so that the establishment of a student sports club in Bali will have an impact on the development of sports achievement at a higher level.